Parasitic zoonoses associated with dogs and cats - Pereira, André (2016)
BACKGROUND: Parasitic diseases of companion animals comprise a group of globally distributed and rapidly spreading illnesses that are caused by a wide range of arthropods, helminths and protozoa. In addition to their veterinary importance, many of these parasites can also affect the human population, due to their zoonotic potential. The aim of the present work was to evaluate the knowledge of Portuguese pet owners regarding the zoonotic potential of parasites that dogs and cats can harbour, most common drugs, frequency of use and reasons for endo- and ectoparasite control. METHODS: Seventy hundred and fifty multiple-choice questionnaires designed to obtain data knowledge about the meaning of zoonosis, knowledge about parasitic diseases and perception regarding their zoonotic potential, as well as the drugs, frequency and reason for deworming their animals were delivered to dog and/or cat owners from non-rural (i.e. urban or semi-urban) and rural parishes who attended veterinary medical centres from continental Portugal. RESULTS: A total of 536 (71.5 %) questionnaires were retrieved. Two hundred and ninety five (56.5 %) responders had heard of zoonosis/zoonoses, but only 184 (35.2 %) knew their meaning. Tick fever, mange, leishmaniosis and ascaridiosis/roundworms were the parasitic diseases from pets most frequently identified. The number of owners who recognized the different parasitoses, who stated to have heard about zoonoses and who were aware of the potential transmission of parasites from animals to humans was significantly higher in those with intermediate (i.e. ≥9 and ≤ 12 years of schooling) and/or higher academic degree (i.e. licentiate, master's and/or doctorate degrees). The combinations of febantel-pyrantel-praziquantel (23.5 %) and milbemycin-praziquantel (34.5 %) were the most widely endoparasitic drugs used in dogs and in cats, respectively. The most common ectoparasiticide used in dogs was a combination of imidacloprid-permethrin (33.4 %), while in cats it was imidacloprid (26.3 %) followed by fipronil (25.4 %). The most used treatment schedule against internal and external parasites in dogs and cats was an administration every three months and the main reason to do it was as a prophylactic purpose. CONCLUSIONS: The majority of Portuguese owners that attended veterinarian clinics use endoparasiticides and ectoparasiticides in/on their pets as a prophylactic measure, although in many cases not in the correct schedule of treatment. In addition, most of them are not aware of the possible transmission of parasites from their dogs and cats to themselves, a fact which highlights the important role of veterinarians in the continuous implementation of effective control measures to reduce the risk of parasitic infections in both humans and companion animals.